WHERE LANGUAGE OF MASSES WEAVES POETRY: SOCIAL AWAKENING IN DHOOMIL’S POETRY - Prof. Ravindra Pratap Singh (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
Sudama Pandey “Dhoomil” is a significant voice in post-1960s Hindi poetry. Poetry, as the energy for life to Dhoomil, extensively reflects the inkling of social awakening and the life of an ordinary man, in every shade of his verses. Dhoomil, as a social reformer, explains how superstitions, social evils, and conservatism can be eradicated through social awakening based on progressive ideas that are much needed to transform society for the general welfare of its individuals. Dhoomil could easily notice that society, as a whole, is an interconnection of human relations where human behaviour is controlled and directed in tune with the expectations of a few axes therein. In such a situation, real knowledge of the contemporary world can be obtained only through adopting a practical approach, as inferred by Dhoomil. In the quest to present social facts without bias, Dhoomil proved that poetry is nothing without its social references. Poetry comes from within society through the complex weave of human relations. It gets influenced and inspired by the overt happenings and undercurrents of society, which closely observe and reflect the dynamics of human relations. Dhoomil’s poetry circumnavigates the bounds of region, linguistic chauvinism, casteism, problems of the youth, and foregrounds the decline in values and morality in general. This disintegration in human relations is closely observed, analysed, and reflected in Dhoomil’s poetry. The present paper offers a note on the major tropes and trajectories in the poetic oeuvre of Sudama Pandey, widely known as “Dhoomil”.